Or, ora, maintenant : perspective temporelle et perspective argumentative - Martin Becker; Marta Donazzan (Discours)
This paper presents a contrastive analysis of the distribution and interpretation of the French adverbs or and maintenant and the Italian adverb ora. Our goal is to describe the parallelism between the temporal and argumentative use of these three adverbs, and to underline at the same time the differences in the use of ora with respect to or / maintenant. We claim that ora and or / maintenant share a common function, which is to update the point of perspective in the temporal structure of the ongoing discourse. Next, we propose that the semantic feature that justifies this updating function is the essential link between the temporal reading and the epistemic reading, which can be considered as the typical result of a process of abstraction of temporal adverbs into discourse connectives.